Sorption Equilibria of Some Transitional Metal Ions on a Chelating Ion-Exchange Resin, Duolite ES 467 - J.P. Rawat; Manisha Bhardwaj (Adsorption Science & Technology)
A simple approach to sorption equilibria on Duolite ES 467 has been applied. Values of the Langmuir constants for Ni II , Cd II , Co II and Fe III have been determined using equilibrium experiments at constant ionic strength and at different temperatures from 20°C to 50°C. Values of the thermodynamic parameters ΔG 0 , ΔH 0 and ΔS 0 have been calculated.